Gel electrolyte, preparation method thereof and lithium ion battery
By using gel electrolytes with high mechanical strength and self-healing ability formed by double bond copolymerization in lithium-ion batteries, the problem of poor contact between traditional gel electrolytes and silicon-based negative electrodes is solved, and the cycling performance of the battery is significantly improved. Security.
Patent Information
- Application Number
- CN202411057549.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2024-12-13
AI Technical Summary
The interface contact between the traditional gel electrolyte and the silicon-based negative electrode is poor, resulting in problems of increased impedance and capacity loss.
Using a gel electrolyte including a copolymer, a lithium salt and an organic solvent, a copolymer is formed by double bond copolymerization of the first monomer and the second monomer, and a crosslinking agent is added to the copolymer to form a network structure. In order to improve mechanical strength and self-repair ability, the mass proportion of the copolymer is controlled between 3% and 49% to inhibit the volume expansion and impedance of the silicon-based negative electrode.
It effectively suppresses the volume expansion effect of the silicon-based negative electrode in the charge and discharge cycle, prevents the powdering of silicon particles, and improves the first-time Coulomb efficiency, capacity retention and safety of lithium-ion batteries.
Smart Images

Figure CN119133586A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a gel electrolyte and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] In clean energy, lithium-ion batteries have many advantages such as high rated voltage, high energy density, long cycle life and low self-discharge, and have been widely used in electric vehicles, energy storage systems, electronic products, etc. Compared with lithium-ion batteries with graphite negative electrodes, lithium-ion batteries with silicon-based negative electrodes have higher energy density and are the key technology for long-range electric vehicles and electronic products.
[0003] At present, most lithium-ion batteries use liquid electrolytes, which causes silicon-based negative electrodes to have volume expansion effect, negative electrode structure pulverization, severe interface impedance, high-temperature flatulence and poor safety during the charge and discharge cycle. Gel electrolyte is a type of semi-solid electrolyte obtained by combining solid electrolyte with liquid electrolyte. It not only has higher structural stability and mechanical properties than liquid electrolyte, but also can effectively inhibit the volume expansion effect of silicon-based negative electrode. It also has higher conductivity and better safety than solid electrolyte, and has broad application prospects. However, the interface contact between traditional gel electrolyte and silicon-based negative electrode is not good, resulting in increased impedance and capacity loss. Summary of the invention
[0004] Based on this, there is a need for a gel electrolyte and a preparation method thereof and a lithium-ion battery to solve the problem that the interface contact between the traditional gel electrolyte and the silicon-based negative electrode is poor, resulting in increased impedance and capacity loss.
[0005] The above-mentioned purpose of the present application is achieved through the following technical solutions:
[0006] In a first aspect of the present application, a gel electrolyte is provided, comprising a copolymer, a lithium salt and an organic solvent;
[0007] The raw materials of the copolymer include a first monomer, a second monomer, a crosslinking agent and an initiator;
[0008] The first monomer and the second monomer form the copolymer through double bond copolymerization;
[0009] The second monomer contains at least one polar group capable of forming intermolecular hydrogen bonds, wherein the polar group includes one of a hydroxyl group, an aldehyde group, a carboxyl group, an amino group, a thiol group, a urea group and an amide group;
[0010] The molar ratio of the first monomer to the second monomer is (0.2-10):1;
[0011] The copolymer accounts for 3% to 49% by mass in the gel electrolyte.
[0012] In some embodiments, the first monomer includes an acrylate monomer; and the second monomer contains one or more of an amino group, a urea group, and an amide group.
[0013] In some embodiments, the first monomer includes one or more of methyl methacrylate, methyl acrylate, ethyl acrylate, ethyl methacrylate, pentaerythritol triacrylate, butyl acrylate, and isobutyl acrylate;
[0014] The second monomer includes one or more of acrylamide, methacrylamide, N-isopropylacrylamide, N,N-methylenebisacrylamide and 2-urea-4[1H]-methylpyrimidinone methacrylate.
[0015] In some embodiments, the ratio of the mass of the cross-linking agent to the total mass of the first monomer and the second monomer is (0.05-5):100.
[0016] In some embodiments, the cross-linking agent includes one or more of polyethylene glycol diester of acrylate, polyethylene glycol dimethacrylate, N,N′-methylenebisacrylamide and polypropylene glycol glycidyl ether.
[0017] In some embodiments, the ratio of the mass of the initiator to the total mass of the first monomer and the second monomer is (0.01-2):100.
[0018] In some embodiments, the initiator includes one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, azobiscyanovaleric acid, dibenzoyl peroxide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride.
[0019] In some embodiments, the lithium salt includes one or more of LiPF6, LiSbF6, LiAsF6, LiBF4, LiPO2F2, LiBOB, LiDFOB, LiDFOP, LiN(SO2F)2, LiN(CF3SO2)2, LiN(CF3CF2SO2)2 and LiC(CF3SO2)2.
[0020] In some embodiments, the organic solvent includes one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene glycol dimethyl ether and 1,3-dioxolane.
[0021] In some embodiments, the ratio of the mass of the lithium salt to the total mass of the lithium salt and the organic solvent is (5-50):100.
[0022] In some embodiments, the gel electrolyte further includes an additive accounting for 0.2% to 30% by mass, and the additive includes one or more of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, lithium difluorooxalatoborate, lithium difluorophosphate, lithium nitrate, 1,3-propane sultone, 1,3-propylene sultone, tris(trimethylsilane) phosphate, tris(trimethylsilane) borate, fluorobenzene and vinyl ethylene carbonate.
[0023] In a second aspect of the present application, a method for preparing the gel electrolyte as described above is provided, comprising the following steps:
[0024] mixing an organic solvent and a lithium salt to prepare an electrolyte;
[0025] Mixing the electrolyte, the first monomer, the second monomer, the crosslinking agent and the initiator to prepare a precursor;
[0026] The precursor is subjected to copolymerization reaction to prepare a gel electrolyte.
[0027] In some embodiments, the precursor is subjected to a copolymerization reaction, comprising the steps of:
[0028] The precursor is injected into the battery cell, and allowed to stand at 20° C. to 100° C. for reaction for 2 h to 48 h.
[0029] In some embodiments, the amount of the precursor injected into the battery cell is 1 g / Ah to 5 g / Ah.
[0030] In a third aspect of the present application, a lithium ion battery is provided, comprising the gel electrolyte as described above, or comprising a gel electrolyte prepared by the method for preparing the gel electrolyte as described above.
[0031] This application has at least the following beneficial effects:
[0032] The present application utilizes the first monomer and the second monomer to carry out double bond copolymerization, and controls the molar ratio of the two to (0.2~10): 1, which can not only promote the interaction of copolymer, lithium salt and organic solvent to form a transparent and uniform gel, avoid phase separation of gel electrolyte and reduce its mechanical strength, but also ensure that the copolymer contains sufficient polar groups to form a complete hydrogen bond network, so that the gel electrolyte has excellent self-repairing ability, and prevents the loss of interface contact and battery performance degradation between the gel electrolyte and the silicon-based negative electrode. At the same time, after adding a cross-linking agent in the double bond copolymerization reaction, the polymer segment in the copolymer can form a network structure, so that the gel electrolyte has high elasticity and high mechanical strength, which can effectively suppress the volume expansion of the silicon-based negative electrode and avoid the degradation of battery performance. At the same time, the mass proportion of the copolymer in the gel electrolyte is controlled at 3%~49%, which can not only suppress the volume expansion of the silicon-based negative electrode, but also prevent the impedance of the electrolyte from being too high and affecting the battery capacity and cycle performance. Therefore, the gel electrolyte provided in the present application introduces a copolymer with high elasticity, high mechanical strength and high cross-linking degree, which can greatly suppress the volume expansion effect of the silicon-based negative electrode during the charge and discharge cycle, prevent the silicon particles from pulverizing and deactivating, and enable lithium-ion batteries using silicon-based negative electrodes with different silicon contents to exhibit high first coulombic efficiency, good capacity retention, small volume change and high safety in the absence of external pressure. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0034] Figure 1 The 30°C cycle performance comparison diagram of the lithium ion batteries of Example 1 and Comparative Examples 1 to 3;
[0035] Figure 2 The 30°C cycle performance comparison diagram of the lithium ion batteries of Example 2 and Comparative Examples 4 to 6;
[0036] Figure 3 The 45°C cycle performance comparison diagram of the lithium ion batteries of Example 3 and Comparative Examples 7-9;
[0037] Figure 4 It is a comparison chart of the thickness changes of Example 3, Comparative Example 4 and Comparative Example 6 within the initial 5 cycles. DETAILED DESCRIPTION
[0038] In order to facilitate the understanding of the present application, the present application is further described in detail below in conjunction with specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0040] In the present application, the meaning of "and / or" includes any and all combinations of one or more related listed items. "At least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present application, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0041] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.
[0042] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0043] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.
[0044] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0045] In the present application, room temperature refers to indoor temperature, normal temperature or general temperature. Generally speaking, the range of room temperature can be any one of the following temperature intervals: 23°C ± 2°C, 25°C ± 5°C or 20°C ± 5°C.
[0046] the term
[0047] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0048] In the present application, when a substituent with the same symbol appears multiple times, each substituent may be the same or different from each other. For example, when a general formula contains multiple R, R may be the same or different from each other.
[0049] "Substituted or unsubstituted" means that the defined group may be substituted or unsubstituted. When the defined group is substituted, it should be understood that the defined group may be substituted by one or more substituents acceptable in the art. Suitable substituents include but are not limited to: C1~C 30 Alkyl, cycloalkyl containing 3 to 20 ring atoms, heterocyclic group containing 3 to 20 ring atoms, aryl containing 6 to 20 ring atoms, heteroaryl containing 5 to 20 ring atoms, silanyl, carbonyl, alkoxycarbonyl, aryloxycarbonyl, carbamoyl, haloformyl, formyl, amino (-N(R)2), urea, cyano, isocyano, isocyanate, thiocyanate, isothiocyanate, hydroxyl, trifluoromethyl, nitro or halogen, and the above groups may be further substituted by substituents acceptable in the art; it is understandable that the R in -N(R)2 is independently substituted by groups acceptable in the art, Including but not limited to: H, C1~C6 alkyl, cycloalkyl containing 3~8 ring atoms, heterocyclyl containing 3~8 ring atoms, aryl containing 5~20 ring atoms or heteroaryl containing 5~10 ring atoms; the C1~C6 alkyl, cycloalkyl containing 3~8 ring atoms, heterocyclyl containing 3~8 ring atoms, aryl containing 5~20 ring atoms or heteroaryl containing 5~10 ring atoms are optionally further substituted by one or more of the following groups: C1~C6 alkyl, cycloalkyl containing 3~8 ring atoms, heterocyclyl containing 3~8 ring atoms, halogen, hydroxyl, urea, nitro or amino.
[0050] The "number of ring atoms" refers to the number of atoms constituting the ring itself of a structural compound (e.g., a monocyclic compound, a condensed ring compound, a cross-linked compound, a carbocyclic compound, a heterocyclic compound) in which atoms are bonded to form a ring. When the ring is substituted by a substituent, the atoms contained in the substituent are not included in the ring atoms. The "number of ring atoms" described below is the same unless otherwise specified. For example, the number of ring atoms of a benzene ring is 6, the number of ring atoms of a naphthalene ring is 10, and the number of ring atoms of a thienyl group is 5.
[0051] "Alkyl" refers to a monovalent residue formed by the loss of a hydrogen atom from a saturated hydrocarbon containing a primary (normal) carbon atom, a secondary carbon atom, a tertiary carbon atom, a quaternary carbon atom, or a combination thereof. Alkyl can represent a straight chain, branched and / or cyclic alkyl group. The carbon number of the alkyl group can be 1 to 50, 1 to 30, 1 to 20, 1 to 10 or 1 to 6. Phrases containing this term, for example, "C1 to C9 alkyl" refers to an alkyl group containing 1 to 9 carbon atoms, and each occurrence can be independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, C7 alkyl, C8 alkyl or C9 alkyl. Suitable examples include, but are not limited to, methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu, s-butyl, -CH(C H3)CH2CH3), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3), 1-pentyl (n-pentyl, -CH2CH2CH2CH2CH3), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH2CH3)2), 2-methyl-2-butyl (-C(CH3)2CH2CH3), 3-methyl-2-butyl (-CH(CH3)CH(CH3)2), 3-methyl-1-butyl (- CH2CH2CH(CH3)2), 2-methyl-1-butyl (-CH2CH(CH3)CH2CH3), 1-hexyl (-CH2CH2CH2CH2CH2CH3), 2-hexyl (-CH(CH3)CH2CH2CH2CH3), 3-hexyl (-CH(CH2CH3)(CH2CH2CH3)), 2-methyl-2-pentyl (-C(CH3)2CH2CH2CH3), 3-methyl-2-pentyl (-CH(CH3)CH( CH3)CH2CH3), 4-methyl-2-pentyl (-CH(CH3)CH2CH(CH3)2), 3-methyl-3-pentyl (-C(CH3)(CH2CH3)2), 2-methyl-3-pentyl (-CH(CH2CH3)CH(CH3)2), 2,3-dimethyl-2-butyl (-C(CH3)2CH(CH3)2), 3,3-dimethyl-2-butyl (-CH(CH3)C(CH3)3, octyl (-(CH2)7CH3).
[0052] "Alkenyl" refers to a group containing at least one unsaturated site, i.e., a carbon-carbon sp 2A monovalent residue formed by a hydrogen atom of a hydrocarbon with a double bond, a secondary carbon atom, a tertiary carbon atom or a ring carbon atom. Suitable examples include, but are not limited to, vinyl (-CH=CH2), allyl (-CH2CH=CH2), cyclopentenyl (-C5H7), 5-hexenyl (-CH2CH2CH2CH2CH=CH2).
[0053] "Alkynyl" refers to a monovalent residue formed by the loss of a hydrogen atom from a hydrocarbon containing a positive carbon atom, a secondary carbon atom, a tertiary carbon atom or a ring carbon atom having at least one unsaturated site, i.e., a carbon-carbon sp triple bond. Suitable examples include, but are not limited to, ethynyl (-C≡CH), propargyl (-CH2C≡CH).
[0054] "Aryl" refers to an aromatic hydrocarbon group derived from an aromatic ring compound containing only carbon atoms by removing a hydrogen atom. It can be a monocyclic aromatic group, a condensed aromatic group, or a polycyclic aromatic group. For polycyclic rings, at least one is an aromatic ring system. For example, "substituted or unsubstituted aromatic group having 6 to 40 ring atoms" refers to a substituted or unsubstituted aromatic group containing 6 to 40 ring atoms, preferably an aromatic group having 6 to 30 ring atoms, more preferably an aromatic group having 6 to 18 ring atoms, and particularly preferably an aromatic group having 6 to 14 ring atoms, and the aromatic group is optionally further substituted. Suitable examples include, but are not limited to, benzene, biphenyl, terphenyl, naphthalene, anthracene, fluoranthene, phenanthrene, triphenylene, perylene, tetracene, pyrene, benzopyrene, acenaphthene, fluorene, triphenylene and their derivatives. It is understandable that multiple aromatic groups may also be interrupted by short non-aromatic units (e.g. <10% non-H atoms, such as C, N or O atoms), specifically acenaphthene, fluorene, or 9,9-diarylfluorene, triarylamine, diaryl ether systems should also be included in the definition of aromatic groups.
[0055] "Heteroaryl" means that at least one carbon atom is replaced by a non-carbon atom based on an aryl group, and the non-carbon atom may be a N atom, an O atom, an S atom, etc. For example, "substituted or unsubstituted heteroaryl having 5 to 40 ring atoms" means a substituted or unsubstituted heteroaryl having 5 to 40 ring atoms, preferably a heteroaryl having 6 to 30 ring atoms, more preferably a heteroaryl having 6 to 18 ring atoms, and particularly preferably a heteroaryl having 6 to 14 ring atoms, and the heteroaryl group may be further substituted. Suitable examples include, but are not limited to, furan, thiophene, benzofuran, benzothiophene, pyrrole, pyrazole, pyridine, pyridine, pyrazine, pyridazine, pyrimidine, triazole, imidazole, oxazole, oxadiazole, thiazole, tetrazole, carbazole, indole, triazine, pyrroloimidazole, pyrrolopyrrole, thienopyrrole, thienothiophene, furopyrrole, furanofuran, thienofuran, benzisoxazole, benzisothiazole, benzimidazole, quinoline, isoquinoline, o-naphthyridine, quinoxaline, phenanthridine, primary idine, quinazoline, quinazolinone, dibenzothiophene, dibenzofuran, carbazole, and derivatives thereof.
[0056] "Heteroalkyl" means that at least one carbon atom is replaced by a non-carbon atom on the basis of an alkyl group, and the non-carbon atom can be an N atom, an O atom, an S atom, etc. For example, if the carbon atom connected to the parent core structure in the alkyl group is replaced by a non-carbon atom, the resulting heteroalkyl group is an alkoxy group (e.g., -OCH3, etc.), an amine (e.g., -NHCH3, -N(CH3)2, etc.) or a thioalkyl group (e.g., -SCH3). If the carbon atom not connected to the parent core structure in the alkyl group is replaced by a non-carbon atom, the resulting heteroalkyl group is an alkyl ether (e.g., -CH2CH2-O-CH3, etc.), an alkylamine (e.g., -CH2NHCH3, -CH2N(CH3)2, etc.) or a thioalkyl ether (e.g., -CH2-S-CH3). If the terminal carbon atom of the alkyl group is replaced by a non-carbon atom, the resulting heteroalkyl group is a hydroxyalkyl group (e.g., -CH2CH2-OH), an aminoalkyl group (e.g., -CH2NH2) or an alkylthiol group (e.g., -CH2CH2-SH).
[0057] "Halogen" or "halo" refers to F, Cl, Br or I.
[0058] "Amino" refers to a monovalent residue having the structural characteristics of the general formula -N(R)2, where each occurrence of R is independently selected from H, substituted or unsubstituted alkyl, substituted or unsubstituted cycloalkyl, substituted or unsubstituted heterocyclyl, etc.
[0059] "Ester group" refers to a monovalent residue having the structural characteristics of the general formula -COOR, wherein R is selected from H, substituted or unsubstituted alkyl, substituted or unsubstituted cycloalkyl, substituted or unsubstituted heterocyclic, etc. For example, if R is selected from H, the resulting ester group is a carboxyl group. If R is selected from substituted or unsubstituted alkyl, the resulting ester group is an alkyl ester group, including but not limited to: methyl ester group (methyl ester group, -COOCH3), ethyl ester group (ethyl ester group, -COOCH2CH3).
[0060] Compared with graphite anodes, lithium-ion batteries using silicon-based anodes can achieve higher energy density. However, most lithium-ion batteries use traditional liquid electrolytes, which causes many problems for silicon-based anodes during the charge and discharge cycle, such as: (1) The volume expansion effect of silicon-based anodes is serious, and the volume change during the charge and discharge cycle can reach 400%; (2) The silicon particles in the silicon-based anode expand, causing the anode structure to pulverize, and the particles lose their electronic conductivity or ion conductivity, resulting in battery failure; (3) The liquid electrolyte will continue to be consumed during the charge and discharge cycle, and a new solid electrolyte interface (SEI) film will be continuously formed, resulting in a serious increase in impedance; (4) The core additive fluoroethylene carbonate (FEC) in the liquid electrolyte is prone to high-temperature flatulence problems; (5) Organic solvents such as ethylene carbonate, dimethyl carbonate, and diethyl carbonate have the defects of being volatile, easy to leak, and highly flammable, which may cause fire or explosion accidents in the event of collision and thermal runaway, and have poor safety.
[0061] In order to deal with the above problems, some studies have combined solid electrolytes and liquid electrolytes to form semi-solid gel electrolytes. Compared with liquid electrolytes, gel electrolytes have higher structural stability and mechanical properties, and can effectively inhibit the volume expansion effect of silicon-based negative electrodes; compared with solid electrolytes, gel electrolytes have higher conductivity and better safety, and have broad application prospects, becoming a transitional product from liquid electrolytes to solid electrolytes. However, the silicon particles in the silicon-based negative electrode continuously undergo expansion-contraction cycles during the insertion and extraction of lithium ions, and are prone to lose interface contact with the gel electrolyte that does not have fluidity. Especially during the contraction process of the silicon-based negative electrode, the interface contact is very poor, resulting in a significant increase in interface impedance and a substantial loss of capacity.
[0062] Based on this, in the first aspect of the present application, a gel electrolyte is provided.
[0063] In some embodiments, the gel electrolyte includes a copolymer, a lithium salt, and an organic solvent;
[0064] The raw materials of the copolymer include a first monomer, a second monomer, a crosslinking agent and an initiator;
[0065] The first monomer and the second monomer form a copolymer through double bond copolymerization;
[0066] The second monomer contains at least one polar group capable of forming intermolecular hydrogen bonds, wherein the polar group includes one of a hydroxyl group, an aldehyde group, a carboxyl group, an amino group, a thiol group, a urea group, and an amide group;
[0067] The molar ratio of the first monomer to the second monomer is (0.2-10):1;
[0068] The mass proportion of copolymers in gel electrolyte is 3%~49%.
[0069] The present application utilizes the first monomer and the second monomer to carry out double bond copolymerization, and controls the molar ratio of the two to (0.2~10): 1, which can not only promote the interaction of copolymer, lithium salt and organic solvent to form a transparent and uniform gel, avoid phase separation of gel electrolyte and reduce its mechanical strength, but also ensure that the copolymer contains sufficient polar groups to form a complete hydrogen bond network, so that the gel electrolyte has excellent self-repairing ability, and prevents the loss of interface contact and battery performance degradation between the gel electrolyte and the silicon-based negative electrode. At the same time, after adding a cross-linking agent in the double bond copolymerization reaction, the polymer segment in the copolymer can form a network structure, so that the gel electrolyte has high elasticity and high mechanical strength, which can effectively suppress the volume expansion of the silicon-based negative electrode and avoid the degradation of battery performance. At the same time, the mass proportion of the copolymer in the gel electrolyte is controlled at 3%~49%, which can not only suppress the volume expansion of the silicon-based negative electrode, but also prevent the impedance of the electrolyte from being too high and affecting the battery capacity and cycle performance. Therefore, the gel electrolyte provided in the present application introduces a copolymer with high elasticity, high mechanical strength and high cross-linking degree, which can greatly suppress the volume expansion effect of the silicon-based negative electrode during the charge and discharge cycle, prevent the silicon particles from pulverizing and deactivating, and enable lithium-ion batteries using silicon-based negative electrodes with different silicon contents to exhibit high first coulombic efficiency, good capacity retention, small volume change and high safety in the absence of external pressure.
[0070] As an example, the molar ratio of the first monomer to the second monomer may be 0.2:1, 0.5:1, 0.8:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1.
[0071] In the present application, if the molar ratio of the first monomer to the second monomer is lower than 0.2:1, it is difficult for the copolymer to form a transparent and uniform gel with the lithium salt and the organic solvent, resulting in the electrolyte being divided into two phases, a liquid electrolyte and a solid copolymer. At this time, there is no interaction between the copolymer and the electrolyte, and it has no mechanical strength, and its performance is almost the same as that of the liquid electrolyte; if the molar ratio of the first monomer to the second monomer is higher than 10:1, the polar group content in the copolymer is too low, and it is difficult to form a polymer hydrogen bond network. The self-healing and self-repairing ability of the gel electrolyte is insufficient, resulting in interface separation between the gel electrolyte and the silicon-based negative electrode, and degradation of the performance of the lithium-ion battery.
[0072] As an example, the mass proportion of the copolymer in the gel electrolyte may be 3%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 49%.
[0073] In the present application, the higher the mass proportion of the copolymer in the gel electrolyte, the more obvious the inhibitory effect on the volume expansion effect of the silicon-based negative electrode, but the increase in the content of the copolymer will increase the internal resistance of the battery, thereby reducing the battery capacity and cycle performance.
[0074] Optionally, the mass proportion of the copolymer in the gel electrolyte is 10% to 20%. As an example, the mass proportion of the copolymer in the gel electrolyte can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.
[0075] In the present application, the mass proportion of the copolymer in the gel electrolyte is controlled within the range of 10% to 20%, at which point the lithium-ion battery can achieve a higher first coulombic efficiency, better cycle performance, and lower volume expansion effect.
[0076] It can be understood that the first monomer and the second monomer form a copolymer through double bond copolymerization, which means that the chemical structure of the first monomer and the chemical structure of the second monomer each independently contain a double bond.
[0077] Optionally, the first monomer and the second monomer each independently have a structure as shown in general formula (I):
[0078] (I);
[0079] wherein each occurrence of R is independently selected from one of H, halogen, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl, substituted or unsubstituted alkoxy, substituted or unsubstituted epoxy, hydroxyl (-OH), aldehyde (-CHO), carboxyl (-COOH), ester (-COOR′), amino (-NR′2), thiol (-SH), and amide (-CONR′2).
[0080] It is understandable that R' in -NR'2 and R' in -CONR'2 are each independently substituted by a group acceptable in the art, including but not limited to: H, C1~C6 alkyl, cycloalkyl containing 3~8 ring atoms, heterocyclic group containing 3~8 ring atoms, aryl containing 5~20 ring atoms, heteroaryl containing 5~10 ring atoms, halogen, hydroxyl, aldehyde, carboxyl, amino, thiol and amide.
[0081] Optionally, in the first monomer, each occurrence of R is independently selected from one of H, C1~C6 alkyl and C2~C6 ester. Further optionally, in the first monomer, each occurrence of R is independently selected from one of H, C1~C3 alkyl and C2~C5 ester. Still further optionally, in the first monomer, each occurrence of R is independently selected from one of H, CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -COOCH3, -COOCH2CH2CH2CH3 and -COOCH2CH(CH3)2.
[0082] Optionally, the first monomer includes an acrylate monomer. The acrylate monomer in the first monomer includes one or more of methyl methacrylate (MMA), methyl acrylate (MA), ethyl acrylate (EA), ethyl methacrylate (MEA), pentaerythritol triacrylate (PETA), butyl acrylate (BA) and isobutyl acrylate (IBA), and may further be methyl methacrylate (MMA).
[0083] Optionally, in the second monomer, each occurrence of R is independently selected from one of H, C1~C6 alkyl, C1~C6 alkenyl, C1~C6 alkynyl, aryl having 6 to 10 ring atoms, heteroaryl having 5 to 10 ring atoms, C1~C6 alkoxy, epoxy having 3 to 6 ring atoms, hydroxyl (-OH), aldehyde (-CHO), carboxyl (-COOH), ester (-COOR′), amino (-N(R′)2), thiol (-SH), urea (-NH-CO-NH-) and amide (-CON(R′)2).
[0084] Optionally, the second monomer contains at least one polar group capable of forming intermolecular hydrogen bonds, and the polar group includes one of a hydroxyl group (-OH), an aldehyde group (-CHO), a carboxyl group (-COOH), an amino group (-N(R′)2), a thiol group (-SH), a urea group (-NH-CO-NH-) and an amide group (-CON(R′)2). Further optionally, the second monomer contains one or more of an amino group (-N(R′)2), a urea group (-NH-CO-NH-) and an amide group (-CON(R′)2).
[0085] Optionally, the second monomer includes one or more of acrylamide (AM), methacrylamide (MAM), N-isopropylacrylamide (IAM), N,N-methylenebisacrylamide (MBA) and 2-urea-4[1H]-methylpyrimidinone methacrylate (UpyMA), and further optionally 2-urea-4[1H]-methylpyrimidinone methacrylate (UpyMA).
[0086] As examples, the structures of acrylamide (AM), N,N-methylenebisacrylamide (MBA) and 2-urea-4[1H]-methylpyrimidinone methacrylate (UpyMA) are shown in general formulas (II) to (IV), respectively:
[0087] (II); (III)
[0088] (IV)
[0089] Among them, acrylamide has an amide group (-CONH2), that is, it contains a polar group that can form intermolecular hydrogen bonds; N,N-methylenebisacrylamide contains two amide groups (-CONH-), that is, it contains two polar groups that can form intermolecular hydrogen bonds; UpyMA contains a urea group (-NH-CO-NH-), an amino group (-NH-) and an amide group (-CON=), that is, it contains four polar groups that can form intermolecular hydrogen bonds, which can play a quadruple hydrogen bonding role, which is beneficial to increase the hydrogen bond content in the copolymer, improve the self-healing properties of the gel electrolyte, and enhance the interface contact between the gel electrolyte and the silicon-based negative electrode, thereby improving the capacity and cycle performance of the battery.
[0090] Optionally, the ratio of the mass of the cross-linking agent to the total mass of the first monomer and the second monomer is (0.05-5): 100. As an example, the ratio of the mass of the cross-linking agent to the total mass of the first monomer and the second monomer can be 0.05:100, 0.1:100, 0.2:100, 0.5:100, 0.8:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100 or 5:100.
[0091] In the present application, adding an appropriate amount of cross-linking agent can promote the formation of a network structure between polymer segments, improve the elasticity and mechanical strength of the gel electrolyte, and effectively inhibit the expansion of the silicon-based negative electrode, thereby avoiding the degradation of battery performance.
[0092] Optionally, the crosslinking agent includes one or more of polyethylene glycol diester of acrylate (PEGDA), polyethylene glycol dimethacrylate (PEGDMA), N,N′-methylenebisacrylamide (MBA) and polypropylene glycol diglycidyl ether (PPGDGE), and may further be polyethylene glycol dimethacrylate (PEGDMA).
[0093] Optionally, the ratio of the mass of the initiator to the total mass of the first monomer and the second monomer is (0.01-2): 100. As an example, the ratio of the mass of the initiator to the total mass of the first monomer and the second monomer may be 0.01:100, 0.02:100, 0.05:100, 0.1:100, 0.2:100, 0.5:100, 0.8:100, 1:100, 1.2:100, 1.5:100, 1.8:100 or 2:100.
[0094] Optionally, the initiator includes a free radical initiator, and the free radical initiator includes one or more of azobisisobutyronitrile (AIBN), azobisisovaleronitrile (AMBN), azobisisoheptanenitrile (ADVN), azobiscyanovaleric acid (ACVA), dibenzoyl peroxide (BPO) and 2,2-azobis(2-methylpropylimidazole) dihydrochloride (AAPH), and further optionally azobisisobutyronitrile (AIBN).
[0095] Optionally, the lithium salt includes one or more of LiPF6, LiSbF6, LiAsF6, LiBF4, LiPO2F2, LiBOB, LiDFOB, LiDFOP, LiN(SO2F)2, LiN(CF3SO2)2, LiN(CF3CF2SO2)2 and LiC(CF3SO2)2, and LiPF6 may be further selected.
[0096] Among them, LiPF6 stands for lithium hexafluorophosphate, which has good ionic conductivity and electrochemical stability and is currently the most commonly used electrolyte lithium salt; LiSbF6 stands for lithium hexafluoroantimonate, which has relatively good thermal stability; LiAsF6 stands for lithium hexafluoroarsenate. LiBF4 stands for lithium tetrafluoroborate, which has good chemical and thermal stability and can be used as an additive for LiPF6-based electrolyte systems to improve the cycle life and electrochemical performance of lithium-ion batteries. LiBOB stands for lithium dioxalate borate, with the chemical formula LiB(C2O4)2, and has the advantages of good thermal stability, good film-forming properties, good electrochemical stability, and good conductivity. LiDFOB stands for lithium difluorooxalate borate, with the chemical formula LiBF2(C2O4), which has the advantages of both lithium dioxalate borate (LiBOB) and LiBF4, can stabilize the solid electrolyte interface (SEI) on the surface of silicon-based negative electrodes, and can also be used as an additive to improve the cycle efficiency and capacity retention rate of batteries. LiDFOP stands for lithium difluorobis(oxalyl)phosphate, with the chemical formula LiPF2(C2O4)2. LiFSI stands for lithium bis(fluorosulfonyl)imide, with the chemical formula LiN(FSO2)2. It has the advantages of high stability (no decomposition below 200°C), excellent low-temperature performance, good hydrolysis stability and more environmentally friendly. It can be used as a lithium salt for the next generation of secondary lithium-ion battery electrolytes to replace lithium hexafluorophosphate. LiTFSI stands for lithium bis(trifluoromethanesulfonyl)imide, with the chemical formula LiN(CF3SO2)2. Compared with LiPF6, LiTFSI has higher electrochemical stability, conductivity, thermal stability and electrode compatibility. It has no corrosive effect on aluminum-based current collectors at higher voltages, does not react with water, can inhibit gas generation, and will not cause battery bloating problems. It can also significantly improve the high-temperature stability of the electrolyte when used only as an additive to traditional electrolyte systems. LiBETI stands for lithium bis(pentafluoroethylsulfonyl)imide, with the chemical formula LiN(CF3CF2SO2)2, which can improve the electrochemical performance and cycle life of lithium-ion batteries.
[0097] Optionally, the organic solvent includes one or more of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), ethylene glycol dimethyl ether (DME) and 1,3-dioxolane (DOL), and further optionally fluoroethylene carbonate (FEC) and dimethyl carbonate (DMC).
[0098] Optionally, the ratio of the mass of the lithium salt to the total mass of the lithium salt and the organic solvent is (5-50):100, and may further be (10-20):100.
[0099] As an example, the ratio of the mass of the lithium salt to the total mass of the lithium salt and the organic solvent may be 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100, or 50:100.
[0100] Optionally, the gel electrolyte also includes additives accounting for 0.2% to 30% by mass, and the additives include one or more of fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl sulfate (DTD), lithium difluorooxalatoborate (LiODFB), lithium difluorophosphate (LiPO2F2), lithium nitrate (LiNO3), 1,3-propane sultone (1,3-Propane Sulfone), 1,3-propylene sultone (1,3-Propylene Sulfone), tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB), fluorobenzene (C6H5F) and vinyl carbonate.
[0101] As an example, the mass proportion of the additive in the gel electrolyte may be 0.2%, 0.5%, 0.8%, 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28% or 30%.
[0102] In a second aspect of the present application, a method for preparing the gel electrolyte as described above is provided.
[0103] In some embodiments, the method for preparing the gel electrolyte comprises the following steps:
[0104] mixing an organic solvent and a lithium salt to prepare an electrolyte;
[0105] Mixing an electrolyte, a first monomer, a second monomer, a cross-linking agent, and an initiator to prepare a precursor;
[0106] The precursor is subjected to copolymerization reaction to prepare a gel electrolyte.
[0107] Optionally, subjecting the precursor to copolymerization reaction comprises the following steps: injecting the precursor into the battery cell, standing at 20° C. to 100° C., and reacting for 2 h to 48 h.
[0108] As an example, the temperature of the copolymerization reaction can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C.
[0109] As an example, the copolymerization reaction time can be 2 h, 4 h, 8 h, 12 h, 16 h, 20 h, 24 h, 28 h, 32 h, 36 h, 40 h, 44 h or 48 h.
[0110] Optionally, the injection amount of the precursor in the battery cell is 1g / Ah~5g / Ah, and can further be 2.5g / Ah.
[0111] As an example, the injection amount of the precursor in the battery cell can be 1g / Ah, 1.5g / Ah, 2g / Ah, 2.5g / Ah, 3g / Ah, 3.5g / Ah, 4g / Ah, 4.5g / Ah or 5g / Ah.
[0112] In a second aspect of the present application, a lithium ion battery is provided, comprising the gel electrolyte as described above, or comprising a gel electrolyte prepared by the method for preparing the gel electrolyte as described above.
[0113] Optionally, a lithium-ion battery includes a positive electrode, a negative electrode, a gel electrolyte and a separator. During the charge and discharge cycle, active lithium ions are intercalated and deintercalated between the positive electrode and the negative electrode; the gel electrolyte conducts lithium ions between the positive electrode and the negative electrode; the separator is located between the positive electrode and the negative electrode to prevent short circuits while allowing lithium ions to pass through.
[0114] Optionally, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer covering at least one surface of the positive electrode current collector.
[0115] Optionally, the positive electrode current collector includes a metal foil or a composite current collector. The metal foil may be aluminum foil; the composite current collector includes a polymer substrate and a metal layer formed on the polymer substrate, the polymer substrate may be made of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE), and the metal layer may be made of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy.
[0116] Optionally, the positive electrode active layer further includes a positive electrode active material, which is a positive electrode active material for lithium ion batteries known in the art. As an example, the positive electrode active material can be at least one of a sulfur positive electrode material, a lithium transition metal oxide, and an olivine structured lithium phosphate. Lithium transition metal oxides include, but are not limited to: lithium cobalt oxide, such as LiCoO2; lithium nickel oxide, such as LiNiO2; lithium manganese oxide, such as LiMnO2 or LiMn2O4; lithium nickel cobalt oxide; lithium manganese cobalt oxide; lithium nickel manganese oxide; lithium nickel cobalt manganese oxide, such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM 333)、LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 ); lithium nickel cobalt aluminum oxide, such as LiNi 0.8 Co 0.15 Al 0.05 O2; and modified compounds of the above-mentioned lithium transition metal oxides. Lithium-containing phosphates with an olivine structure include, but are not limited to: lithium iron phosphate, such as LiFePO4 (LFP); a composite material of lithium iron phosphate and carbon; lithium manganese phosphate, such as LiMnPO4; a composite material of lithium manganese phosphate and carbon; lithium iron manganese phosphate; a composite material of lithium iron manganese phosphate and carbon; and modified compounds of the above-mentioned lithium-containing phosphates with an olivine structure. The modified compound of each material may be at least one of doping modification and surface coating modification.
[0117] Optionally, the positive electrode active layer further includes a binder to improve the bonding strength between the positive electrode active layer and the positive electrode current collector. The binder includes at least one of polyvinylidene fluoride (PVDF), sodium alginate (SA), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), hydrogenated nitrile rubber (HNBR), polytetrafluoroethylene (PTFE), and polyacrylic acid (PAA).
[0118] Optionally, the positive electrode active layer further includes a conductive agent, and the conductive agent includes at least one of conductive carbon, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon quantum dots, carbon nanotubes, graphene and carbon nanofibers.
[0119] Optionally, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer covering at least one surface of the negative electrode current collector.
[0120] Optionally, the negative electrode current collector includes a metal foil or a composite current collector. The metal foil in the negative electrode current collector may be copper foil. The composite current collector in the negative electrode current collector is substantially the same as that in the positive electrode current collector and will not be described in detail.
[0121] Optionally, the negative electrode active layer includes a negative electrode active material, and the negative electrode active material includes at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-oxygen-carbon composite, silicon-nitrogen composite, silicon oxide material, and silicon alloy material. It can be understood that the negative electrode active material in the present application contains silicon element, which is usually called a silicon-based negative electrode.
[0122] Optionally, the negative electrode active layer further includes a binder, and the binder includes at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0123] Optionally, the negative electrode active layer further includes a conductive agent, and the conductive agent includes at least one of conductive carbon, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon quantum dots, carbon nanotubes, graphene and carbon nanofibers.
[0124] It is understandable that the separator can be a porous separator with good chemical stability and mechanical stability; at the same time, the separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without special restrictions.
[0125] Optionally, the material of the diaphragm includes at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0126] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.
[0127] Example 1
[0128] In this embodiment, the preparation method of the lithium ion battery using the gel electrolyte is as follows:
[0129] (1) Preparation of electrolyte: An organic solvent and a lithium salt are mixed to obtain an electrolyte; wherein the organic solvent is composed of fluoroethylene carbonate (FEC) and dimethyl carbonate (DMC) in a mass ratio of 3:7, and the lithium salt is LiPF6. The mass proportion of the lithium salt in the electrolyte is 13%, and the concentration is about 1 mol / L.
[0130] (2) Preparing a precursor: adding a first monomer, a second monomer, a crosslinking agent and an initiator into an electrolyte to obtain a precursor; wherein the first monomer is methyl methacrylate (MMA), the second monomer is 2-urea-4[1H]-methylpyrimidinone methacrylate (UPyMA), and the molar ratio of the first monomer to the second monomer is 4:1; the crosslinking agent is polyethylene glycol dimethacrylate (PEGDMA), and the ratio of the mass of the crosslinking agent to the total mass of the two monomers is 1:100; the initiator is azoisobutylonitrile (AIBN), and the ratio of the mass of the initiator to the total mass of the two monomers is 0.5:100.
[0131] (3) Preparation of positive electrode sheet: The positive electrode active material NCM811, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF) were mixed uniformly in a mass ratio of 93:4:3, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and the aluminum lead wire was welded with an ultrasonic welder to obtain a positive electrode sheet. The thickness of the positive electrode sheet was 120 μm~150 μm, and the loading amount of the positive electrode active material was about 17.5 mg / cm 2 .
[0132] (4) Preparation of negative electrode sheet: Silicon-carbon composite material (specific capacity of 450 mAh / g), conductive carbon black Super-P and binder polyacrylic acid (PAA) were mixed evenly in a mass ratio of 90:5:5, and then dispersed in deionized water to obtain negative electrode slurry; the negative electrode slurry was coated on both sides of the copper foil, dried, roll-pressed, and welded with nickel lead wires using an ultrasonic welder to obtain a negative electrode sheet. The surface density and surface capacity of the negative electrode sheet were calculated based on the surface capacity of the prepared positive electrode, and the N / P ratio was controlled at 1.15.
[0133] (5) Preparation of battery cells: A polyethylene microporous membrane with a thickness of 20 μm is placed between the positive electrode sheet and the negative electrode sheet as a separator. The sandwich structure consisting of the positive electrode sheet, the negative electrode sheet and the separator is then wound up. The wound body is then flattened and placed in an aluminum-plastic film. After the lead wires of the positive and negative electrode sheets are led out respectively, the aluminum-plastic film is sealed by hot pressing to obtain a battery cell ready for liquid injection.
[0134] (6) Preparation of gel electrolyte: In a glove box with a dew point controlled below -40°C, inject the precursor into the battery cell at an injection volume of 2.5 g / Ah. After the precursor fully infiltrates the battery cell, clamp the soft-pack battery cell with a large clamp and then place it in an oven at 60°C for 8 hours to perform an in-situ polymerization reaction to obtain a fully cured gel electrolyte and a lithium-ion battery to be formed.
[0135] (7) Battery formation: 0.05C constant current charging for 180 min, 0.1C constant current charging for 180 min, standing for 24 h before shaping and sealing, and then further charging at 0.2C constant current to 4.25 V. After standing at room temperature for 24 h, discharge at 0.2C constant current to 2.5 V to obtain a formed lithium-ion battery.
[0136] Embodiments 2 to 12
[0137] Examples 2 to 12 are substantially the same as Example 1, except that the differences are shown in Table 1.
[0138] Comparative Examples 1 to 13
[0139] Comparative Examples 1 to 13 are substantially the same as Example 1, except that the differences are shown in Table 2.
[0140] Test Case
[0141] The formed lithium-ion battery was tested as follows, and the test results are listed in Figure 1~Figure 4 and Table 3.
[0142] (1) First coulombic efficiency: In the battery formation step, the charge capacity is Q1, the discharge capacity is Q2, and the first coulombic efficiency is expressed as Q1 / Q2. The first coulombic efficiency reflects the extent of side reactions between the electrolyte and the electrode during the first charge of the battery.
[0143] (2) Number of cycles when the capacity retention rate reaches 80%: At 30°C, charge to 4.25V at a constant current of 0.5C, then charge at a constant voltage until the current drops to 0.05C, then discharge to 2.7V at a constant current of 0.5C, and repeat this cycle for at least 500 cycles. Record the number of cycles when the capacity retention rate drops to 80%. The capacity retention rate is calculated as follows: Capacity retention rate = (discharge capacity at the 300th week / initial nominal capacity of the battery) × 100%.
[0144] (3) Thickness change of soft-pack battery after 5 cycles: The battery after capacity division was placed in an in-situ thickness tester at 30°C, and charged and discharged at a current rate of 0.5C / 0.5C for 5 weeks, and the change of battery thickness with the number of cycles was recorded.
[0145] (4) Puncture test results: In the soft-pack battery puncture test device, a high-temperature resistant steel needle of Φ5mm~Φ8mm is used to penetrate the battery plate at a speed of (25±5)mm / s in a direction perpendicular to the battery plate. The penetration position should be close to the geometric center of the punctured surface. The steel needle stays in the battery for 10 minutes and the battery performance is observed.
[0146] The applicant has verified through a series of experiments that the liquid electrolyte is charged and discharged in a silicon-based negative electrode soft-pack battery. If there is no external pressure, the battery capacity will decay sharply. This is because the silicon particles expand and shrink during the process of lithium removal and lithium insertion, resulting in irreversible void growth and conductive network failure (such as partial loss of contact with conductive carbon and current collector). Under sufficient external pressure, the volume expansion effect of the silicon-based negative electrode is effectively limited to the damage to the conductive network, because the external pressure can continuously maintain the contact between the silicon particles and the current collector and conductive carbon, and can also inhibit the volume expansion of the negative electrode to a certain extent, maintaining close contact between the silicon particles and the electrolyte, and maintaining Li + Pathway. However, the application of external pressure requires splints and other fixtures, which occupy additional weight and volume, reducing the energy density of the overall battery module. Using only MMA for in-situ polymerization, the gel electrolyte formed can provide sufficient cross-linking network and viscosity, so that the battery can still be stably cycled even without external pressure, and the capacity is almost the same as that of the liquid electrolyte; even when there is external pressure on the liquid electrolyte, the gel battery in the pressure-free state is still more cycle stable and safer than it. However, when the silicon content in the silicon-based negative electrode is increased (that is, the specific capacity is increased), the compatibility of the gel formed by only MMA polymerization with the silicon-based negative electrode becomes worse, which is reflected in the reduction of the initial capacity of the battery and the cycle attenuation. The use of MMA and UpyMA for copolymerization to prepare the gel electrolyte can significantly improve the initial capacity and cycle stability of the high silicon-based negative electrode system. This may be due to the fact that the chemical structure of UpyMA contains four polar groups that can form intermolecular hydrogen bonds, and multiple hydrogen bonds improve the contact between the gel electrolyte and the electrode interface.
[0147] Through Example 1 and Comparative Examples 1 to 3, it can be found that in the absence of external pressure, the first efficiency of the liquid battery without PMMA and UpyMA is only 75.6%, and it decays to less than 80% capacity in only 121 cycles, and the overall battery thickness expands sharply by 21.1% (Comparative Example 1). After applying external pressure, the performance is significantly improved, with an initial efficiency of 82.9% and 80% after 721 cycles (Comparative Example 2). This reflects the importance of external pressure for silicon-based negative electrode batteries. When 15% MMA is mixed with the electrolyte for in-situ polymerization, the overall electrolyte presents a semi-solid state with non-flowability and has considerable mechanical strength. In the cycle process without external pressure, its first efficiency reaches 83.8%, the number of cycles with 80% retention rate reaches 832, and the thickness only increases by 2.9% after 5 cycles (Comparative Example 3). It is worth noting that after replacing 1 / 5 of the MMA molecules with an equal amount of UpyMA and copolymerizing (4:1), the soft-pack battery showed the best performance, with an initial efficiency of 85.5%, an 80% retention rate of >1000 cycles, and a thickness increase of only 0.04% in the initial 5 cycles (Example 1). This reflects the improvement of UpyMA based on PMMA, that is, it can provide higher mechanical strength and closer interface contact.
[0148] The applicant also compared the application of the above four electrolytes in different silicon content negative electrode systems. In the SiO (600mAh / g) system, it can be found through Example 2 and Comparative Examples 4 to 6 that in the absence of external pressure, the first efficiency of the liquid battery without PMMA and UpyMA is only 70.5%, and it decays to less than 80% capacity in only 23 cycles, and the overall battery thickness expands sharply by 27.5% (Comparative Example 4). After applying external pressure, the performance is significantly improved, with an initial efficiency of 83.8% and a cycle of 711 weeks to reach 80% (Comparative Example 5). This also reflects the importance of external pressure for silicon-based negative electrode batteries. When the applicant used 15% MMA mixed with the electrolyte for in-situ polymerization, the overall electrolyte showed a semi-solid state with no fluidity and had considerable mechanical strength. In the circulation process without external pressure, although its first efficiency reached 82.4%, it did not increase compared to Comparative Example 5, and the initial capacity was only about 1200 mAh, which is a large gap compared to the theoretical nominal capacity of 1500 mAh. The applicant believes that this is because PMMA itself is hard and lacks flexibility and self-healing properties, which causes the silicon negative electrode to break away from the interface contact with the solid electrolyte during the expansion cycle, resulting in huge interface impedance and low capacity. After using MMA:UpyMA=4:1 copolymerization, its electrochemical performance has been most significantly improved: the first efficiency reached 83.5%, the number of cycles with 80% retention rate reached 943 times, and the initial 5-cycle thickness growth was only 0.44% (Example 2).
[0149] In the SiO (900mAh / g) system, it can be found through Example 3 and Comparative Examples 7 to 9 that in the absence of external pressure, the first efficiency of the liquid battery without PMMA and UpyMA is only 53.7%, and it decays to less than 80% capacity in just 13 cycles, and the overall battery thickness expands sharply by 34.2% (Comparative Example 7). After applying external pressure, the performance is significantly improved, with an initial efficiency of 81.9% and 80% after 305 cycles (Comparative Example 8). This further reflects the importance of external pressure for silicon-based negative electrode batteries. When the applicant used 15% MMA mixed with the electrolyte for in-situ polymerization, the overall electrolyte presented an illiquid semi-solid state with considerable mechanical strength. In the circulation process without external pressure, although its first efficiency reached 78.6%, it did not improve compared to Comparative Example 8, and the initial capacity was only about 3000 mAh, which is a large gap compared to the theoretical nominal capacity of 3400mAh, and it decayed significantly in subsequent cycles. The applicant believes that the interface problem caused by PMMA separating from the gel electrolyte during the expansion and contraction of the silicon negative electrode is more serious in a high-content silicon system. After using MMA:UpyMA=4:1 copolymerization, its electrochemical performance has been most significantly improved: the first efficiency reached 82.4%, the number of cycles with 80% retention rate reached 561 times, and the initial 5-cycle thickness growth was only 1.69% (Example 3).
[0150] In addition, the applicant explored the effect of different copolymer mass ratios on the performance of the gel electrolyte: Through Examples 2, 4 and 5, it can be found that as the copolymer content increases from 15% to 45%, its first coulombic efficiency decreases as the polymer content increases. This is because the copolymer increases the internal resistance of the battery, resulting in a decrease in capacity, and the cycle performance also decreases slightly as the internal resistance of the battery increases. At the same time, as the copolymer content increases, the electrolyte hardness and toughness are enhanced, and the thickness growth of the battery cycle gradually decreases. As the polymer content decreases (Examples 2, 6 and 7), the battery cycle performance decreases slightly, and the thickness expansion gradually increases. This shows that the higher the copolymer mass ratio, the more obvious the inhibitory effect on the battery thickness expansion. The copolymer mass ratio is preferably 10% to 20%, at which time the battery has the highest first coulombic efficiency, the most stable cycle performance and lower thickness expansion. It can be seen from comparative examples 10 and 11 that if the copolymer content is too low (≤1%), the mechanical strength of the electrolyte is too low to suppress the expansion of the silicon negative electrode, resulting in significant cycle degradation; if the copolymer content is too high (≥50%), the electrolyte impedance is too large. Although the thickness expansion can be significantly suppressed, the battery capacity and cycle performance are extremely degraded, making it impossible to apply it in practice.
[0151] By comparing Examples 2, 8 to 10 and Comparative Example 12, it can be seen that the molar ratio of MMA to UpyMA needs to be controlled between (0.2 to 10): 1. If the molar ratio is <0.2: 1, it is difficult for the copolymer to form a transparent and uniform gel with the electrolyte, resulting in the electrolyte being divided into two phases, the electrolyte and the solid copolymer. At this time, there is no interaction between the copolymer and the liquid molecules of the electrolyte, and the copolymer does not have mechanical strength, resulting in its performance being almost the same as that of the liquid electrolyte. If the molar ratio is >10: 1, the hydrogen bond content is too low to form a polymer hydrogen bond network, and the self-healing ability and mechanical properties of the gel electrolyte are insufficient, resulting in interface shedding and performance degradation.
[0152] By comparing the copolymer content, the molar ratio of the two monomers and the results of the needle puncture safety test, it can be found that with the increase of the copolymer content and the molar ratio of the UpyMA monomer, the safety performance of the battery gradually improves. However, considering the battery capacity and cycle performance, the copolymer content is preferably 10%~20%, and the molar ratio of MMA to UpyMA is preferably between (0.2~10):1.
[0153] By comparing Example 2 and Comparative Example 13, it can be found that at the same polymer content and the same monomer molar ratio, if 1% of the cross-linking agent is not added, a network structure cannot be formed between the polymer segments, the formed gel has no elasticity and mechanical strength, and cannot inhibit the expansion of the silicon negative electrode, thereby significantly deteriorating the battery performance.
[0154] Through Examples 11 and 12, it can be found that in addition to UpyMA, other monomers that can form intermolecular hydrogen bonds, such as amide monomers such as acrylamide and N,N-methylenebisacrylamide, also have similar functions, namely, providing hydrogen bonding in acrylic ester copolymers, improving the mechanical strength of the polymer electrolyte, and improving the interface contact between the silicon-based negative electrode and the electrolyte, thereby improving the cycle performance and safety performance of the Si-based soft-pack battery.
[0155] Through Example 2 and Example 13, it can be found that adding 2% by weight of lithium difluorooxalatoborate (LiDFOB) to the existing gel electrolyte formula can further improve the first coulombic efficiency of the battery, improve the cycle to more than 1000 cycles, and maintain lower thickness expansion and good safety performance. This shows that the improvement effect of this type of lithium salt additive on the battery in the gel electrolyte is similar to that in the traditional liquid electrolyte system.
[0156] In summary, in silicon-based negative electrode batteries, gel electrolytes have higher mechanical properties than liquid electrolytes, which can maintain long-term stable cycles under zero pressure, improving energy density from the perspective of battery modules. In high-energy density batteries with increased silicon content, gels with only PMMA are no longer applicable because PMMA lacks flexibility and interface self-healing properties. The gel after adding a certain amount of UpyMA has higher mechanical strength and better interface affinity, allowing silicon-based negative electrode gel batteries to exhibit the best electrochemical and safety performance.
[0157] Table 1. Variables of Examples 1 to 13
[0158]
[0159] Table 2. Variables of Comparative Examples 1 to 13
[0160]
[0161] Table 3. Performance comparison of examples and comparative examples
[0162]
[0163]
[0164] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0165] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the attached claims.
Claims
1. A gel electrolyte, characterized in that: including a copolymer, a lithium salt and an organic solvent; The raw materials of the copolymer include a first monomer, a second monomer, a crosslinking agent and an initiator; The first monomer and the second monomer form the copolymer through double bond copolymerization; The second monomer contains at least one polar group capable of forming intermolecular hydrogen bonds, wherein the polar group includes one of a hydroxyl group, an aldehyde group, a carboxyl group, an amino group, a thiol group, a urea group and an amide group; The molar ratio of the first monomer to the second monomer is (0.2-10):1; The copolymer accounts for 3% to 49% by mass in the gel electrolyte.
2. The gel electrolyte according to claim 1, characterized in that The first monomer includes an acrylic ester monomer; the second monomer contains one or more of an amino group, a urea group and an amide group.
3. The gel electrolyte according to claim 2, characterized in that The first monomer includes one or more of methyl methacrylate, methyl acrylate, ethyl acrylate, ethyl methacrylate, pentaerythritol triacrylate, butyl acrylate and isobutyl acrylate; The second monomer includes one or more of acrylamide, methacrylamide, N-isopropylacrylamide, N,N-methylenebisacrylamide and 2-urea-4[1H]-methylpyrimidinone methacrylate.
4. The gel electrolyte according to any one of claims 1 to 3, characterized in that One or more of the following conditions are met: (1) The ratio of the mass of the cross-linking agent to the total mass of the first monomer and the second monomer is (0.05-5):100; (2) The crosslinking agent includes one or more of polyethylene glycol diester of acrylate, polyethylene glycol dimethacrylate, N,N′-methylenebisacrylamide and polypropylene glycol glycidyl ether; (3) The ratio of the mass of the initiator to the total mass of the first monomer and the second monomer is (0.01-2):100; (4) The initiator includes one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptylnitrile, azobiscyanovaleric acid, dibenzoyl peroxide and 2,2-azobis(2-methylpropylimidazole) dihydrochloride.
5. The gel electrolyte according to any one of claims 1 to 3, characterized in that: One or more of the following conditions are met: (1) The lithium salt includes one or more of LiPF6, LiSbF6, LiAsF6, LiBF4, LiPO2F2, LiBOB, LiDFOB, LiDFOP, LiN(SO2F)2, LiN(CF3SO2)2, LiN(CF3CF2SO2)2 and LiC(CF3SO2)2; (2) The organic solvent includes one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene glycol dimethyl ether and 1,3-dioxolane; (3) The ratio of the mass of the lithium salt to the total mass of the lithium salt and the organic solvent is (5-50):
100.
6. The gel electrolyte according to any one of claims 1 to 3, characterized in that: The gel electrolyte also includes an additive with a mass ratio of 0.2% to 30%, and the additive includes one or more of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, lithium difluorooxalatoborate, lithium difluorophosphate, lithium nitrate, 1,3-propane sultone, 1,3-propylene sultone, tris(trimethylsilane)phosphate, tris(trimethylsilane)borate, fluorobenzene and vinyl ethylene carbonate.
7. A method for preparing a gel electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: mixing an organic solvent and a lithium salt to prepare an electrolyte; Mixing the electrolyte, the first monomer, the second monomer, the crosslinking agent and the initiator to prepare a precursor; The precursor is subjected to copolymerization reaction to prepare a gel electrolyte.
8. The method for preparing a gel electrolyte according to claim 7, characterized in that: The precursor is subjected to a copolymerization reaction, comprising the following steps: The precursor is injected into the battery cell, and allowed to stand at 20° C. to 100° C. for reaction for 2 h to 48 h.
9. The method for preparing a gel electrolyte according to claim 8, characterized in that: The injection amount of the precursor in the battery core is 1g / Ah~5g / Ah.
10. A lithium ion battery, characterized in that: The invention comprises a gel electrolyte as claimed in any one of claims 1 to 6, or a gel electrolyte prepared by the method for preparing a gel electrolyte as claimed in any one of claims 7 to 9.
